Antineoplastic agents exacerbate periodontal inflammation and aggravate experimental periodontitis. (23rd April 2019) - Gusman, David Jonathan Rodrigues; Ervolino, Edilson; Theodoro, Letícia Helena; Garcia, Valdir Gouveia; Nagata, Maria José Hitomi; Alves, Breno Edson Sendão; de Araujo, Nathalia Januario; Matheus, Henrique Rinaldi; de Almeida, Juliano Milanezi
Abstract: Aim: This study evaluated the effects of 5‐fluorouracil (5‐FU) and cisplatin (CIS) in healthy periodontal tissues and in the early stages of experimental periodontitis (EP) in rats. Methods: One hundred and eighty male rats were divided into three groups, which were submitted to the following systemic treatments: physiological saline solution (PSS); CIS and 5FU. Each group was subdivided into two subgroups: without (NEP) and with (EP) induction of EP. Animals were euthanized at 3, 5 and 7 days post‐treatment. Histological, histometric (percentage of bone in the furcation [PBF]) and immunohistochemical (for tumour necrosis factor‐α, interleukin‐1β and receptor activator of nuclear factor‐κB ligand) analyses were performed. Data were statistically analysed. Results: CIS‐NEP and 5FU‐NEP showed more inflammation than PSS‐NEP at 3, 5 and 7 days. CIS‐EP and 5FU‐EP showed more inflammation and lower PBF than PSS‐EP at all periods of evaluation. 5FU‐EP showed lower PBF than CIS‐EP at 5 and 7 days. Conclusion: 5‐FU and CIS exacerbated periodontal inflammation and aggravated the progression of EP in its early stages.